Recurrent hepatitis C treatment with direct acting antivirals – a real life study at a Brazilian liver transplant center - Zanaga,L.P. (2019)
Recurrent hepatitis C (HCV) after liver transplantation (LT) is an important cause of morbidity and mortality. Antiviral treatment is recommended to avoid unfavorable outcomes. Direct-acting antivirals (DAA) have transformed HCV treatment, with higher efficacy and fewer side-effects than interferon-based therapies traditionally used. To evaluate DAA treatment outcomes at a Brazilian transplant unit, data of patients who finished HCV treatment at the Liver Transplant Unit of the University of Campinas were analyzed. Treatment consisted of sofosbuvir, daclatasvir, and ribavirin, for 12 or 24 weeks, according to the national guidelines. Fifty-five patients completed antiviral treatment and 54 had HCV-viral load results available. The majority of patients were male (78%), 58 years old on average, 65% had hepatocellular carcinoma (HCC) before LT, and 67% were interferon treatment-experienced. Most patients had HCV genotype 1 (65%), 35% had genotype 3, and started treatment on an average of 38 months after LT (range: 2–228). Fifty-eight percent were treated for 12 weeks and 42% for 24 weeks, using a mean dose of ribavirin of 10.1 mg/kg (4.2–16.1). There were no treatment interruptions due to serious side effects. The sustained virological response rate was 98%. Only one patient relapsed, a genotype 3 cirrhotic treated for 12 weeks. The average follow-up after starting antivirals was 20 months. There were no recurrences of HCC, but there was one rejection episode and one cirrhosis decompensation episode, both 12 weeks after treatment. DAA treatment is safe and effective in the post-LT setting and was not associated to HCC recurrence in the cohort studied.